Modifikasi Mesin Las Titik Portable dengan Menambahkan Dudukan dan Pedal untuk Menunjang Kegiatan Pratikum Mahasiswa - Subarjo Subarjo; Tri Widodo (Jurusan Teknologi Pertanian, 2020)
Welding is one way to connect two metal parts permanently by using heat power. This heat power is needed to melt the basic material to be connected and welding wire as filler material. After it has cooled and frozen, a strong and permanent bond is formed. One way that is often recommended in this industry is spot welding. Welding point in the Lampung State Polytechnic Metal and Automotive Laboratory, the operating system is done by squatting so that it is easily tired. So with that conditions this research is modified into a table spot welding by modifying the lever with a pedal.Â The objectives of this research are comparing the working time of a portable spot welding machine with a table spot welding machine using the pedal system, to get the efficiency of welding work time using a table spot welding machine using the pedal system, and to reduce work fatigue. The result showed for the pedal point table welding machine, it takes 0.512 minutes for 0.8mm plates, while for 1.0mm plates it takes 0.61 minutes, while for portable welding machines it takes 1.185 seconds for 0.8 plate thickness mm and 1,314 seconds for the 1.0 mm plate.Â Keywords: welding, spot welding, welding wire